GOVERNMENT POLICIES STRATEGY IN DEALING WITH THE COVID-19 OUTBREAK: LESSONS FROM TAIWAN’S EXPERIENCE - Fridayani Helen Dian (OISAA, 2021)
This article contributes to the field of public policy and provides a concrete figure of how the government's policy strategy in combating the Covid-19 epidemic. Taiwan was very much situated to respond rapidly and viably to the Covid-19 outbreak. Taiwan's involvement in SARS in 2003 helped drive the government to respond quickly to the rising emergency. Taiwan is not a member of the WHO, but the strategies carried out by the Taiwanese government can provide lessons and examples for other countries. The method used in this research are observation and literature study, looking for theoretical references that are relevant to cases or problems regarding the handling of the covid-19 outbreak in Taiwan. The aftereffects of this study demonstrate that, Taiwan is not just a guide of majority rule government, yet in addition living evidence that control of a rising infection can be accomplished through science, innovation, and democratic governance. No radical despotic measures are required. The government responded rapidly and conclusively in January, by establishing early travel limitations, turning out testing, and stating control of clinical stockpile lines. Taiwan additionally perceived the potential for human-to-human transmission before China or the WHO did. Through these measures, Taiwan has had the option to maintain a strategic distance from the kind of clearing lockdowns actualized the world over.